The impact of flexible working hours toward employee's productivity in Politeknik Kota Bharu, Kelantan / Siti Sofia Ainuddin - Ainuddin, Siti Sofia (Faculty of Business Management, 2017)
The purpose of this paper is to investigate the impact of flexible working hours toward employee's productivity in Politeknik Kota Bharu. A total of 100 questionnaires were distributed to the academician employees using stratified sampling. The response rate is 83%. Researcher discovered a flexible working hour (FWHs) was significantly and positively gives impact to employee's productivity. It also revealed that a flexible working hour has strong relationship to employee's productivity. Theoretically, this paper has contributed to the company, body of knowledge and researcher on the flexible working hours and productivity issues. Practically, researcher suggests management of companies to consider implementing flexible working hour to fulfill the need of their employees. As conclusion, this paper has revealed the importance of flexible working hours policies in increasing employee's productivity.